Electrochemical reduction of CO2 by In doped- SnO2 nanoparticles with high stability and activity toward selective formic acid formation - Jumaa A. Aseeri; Mabrook S. Amer; Karthik Peramaiah; Kuo-Wei Huang; Abdullah M. Al-Mayouf (Journal of CO2 Utilization, 2025)
SnO2 catalysts have been identified as active electrocatalysts for formate (HCOO─) production in electrochemical CO2 reduction reactions (eCO2RR). Nevertheless, it is a tremendous challenge to develop SnO2 that is durable under the working conditions of eCO2RR. Here, we present an effective method for the development of indium-doped SnO2 porous nanoparticles (In (X%) - SnO2 (NPs)), which are effective electrocatalysts for elevating CO2 reduction to HCOO-. We prepared In (X%)-SnO2 (NPs) with a minimal content of In (≤ 5 %) via the facile evaporation-induced co-assembly (EICA) approach followed by calcination under N2 and Air atmosphere. Compared with bare SnO2 (NPs), In(1 %)-SnO2 (NPs) exhibits a significantly enhanced CO2 reduction activity with a higher partial current density at −1.2 V vs RHE (-23.56 mA cm−2), and higher faradic efficiency (∼98 %) for formic acid production at a wide range of potential (-0.9 to −1.2) V vs RHE. Moreover, the In(1 %)-SnO2 (NPs) also showed excellent stability for over 50 h and a higher faradic efficiency of 95 % at −0.93 V vs RHE for formate production. It is believed that the porous structure of In(X%)-SnO2 (NPs) contributes to the enhanced faradic efficiency and stability, and the uniform surface activation of Sn-In/SnO2 on a homogeneously distributed In(X%)-SnO2 (NPs) crystal leads to an increase in surface area, oxygen vacancies, electron transfer efficiency, and catalytic activity for eCO2RR. This approach, which incorporates a porous structure, oxygen vacancies, and element doping, provides an effective route for developing highly active electrocatalysts and enhancing electrocatalytic performance.